Gardner’s Syndrome, a variant of familial adenomatous polyposis: a case report (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2022)
Introduction: Gardner’s syndrome is a rare, autosomal dominant disease associated with the mutation of the Adenomatous polyposis coli (APC) gene, characterized by colonic polyposis with a histopathology compatible with adenoma, associated with mesenchymal tumor, such as desmoid type, osteomas and dental alterations. Extraintestinal manifestations may be the first findings, being important knowledge and disclosure of the clinical condition, allowing early diagnosis, adequate management and family investigation. Case report: This case report aims to describe the clinical case of familial adenomatous polyposis with a variant compatible with Gardner’s Syndrome, in a patient with extra intestinal manifestations with desmoid tumor, supernumerary teeth and osteomas, ongoing at the Digestive System Unit of the Cassiano Antônio Moraes University Hospital, Federal University of Espirito Santo – Brazil, in addition to a literature review in the Pubmed databases to alert the health care community, especially doctors, about the phenotype presented in Gardner’s Syndrome, enabling early diagnosis.